2020
DOI: 10.1002/hup.2774
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of acute doses of benzodiazepines as a model of anterograde amnesia

Abstract: Objective: Acute administration of benzodiazepines is considered a pharmacological model of general organic anterograde amnesias (OAA). We sought to determine which type of amnesia these drugs best model by comparing the effects of diazepam with those reported in amnesiacs regarding working memory capacity (WMC), susceptibility to retroactive interference (RI), and accelerated forgetting. Methods:In this double-blind, parallel-group design study, 30 undergraduates were randomly allocated to acute oral treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 125 publications
(207 reference statements)
0
4
0
Order By: Relevance
“…Specifically, while repression (or dissociative amnesia) is still criticized for its validity ( Otgaar et al, 2019 ; Patihis et al, 2019 ; Battista et al, 2023 ; Pope et al, 2023 ), other explanations besides false memories are being put forth to explain recovered memories of trauma that may occur outside of a therapeutic setting. For example, some memories may not be fully encoded, due for example to stress that may limit the integration of certain information ( Deffenbacher et al, 2004 ), or the use of substances such as alcohol or drugs (see Kloft et al, 2021 ; Segura et al, 2021 ). Another example is that in some cases the recovered memories of trauma are in fact continuous memories (i.e., memories of events that people feel they have always known occurred) that have only been reinterpreted as abuse with the time and maturity to understand the event ( McNally and Geraerts, 2009 ; McNally, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, while repression (or dissociative amnesia) is still criticized for its validity ( Otgaar et al, 2019 ; Patihis et al, 2019 ; Battista et al, 2023 ; Pope et al, 2023 ), other explanations besides false memories are being put forth to explain recovered memories of trauma that may occur outside of a therapeutic setting. For example, some memories may not be fully encoded, due for example to stress that may limit the integration of certain information ( Deffenbacher et al, 2004 ), or the use of substances such as alcohol or drugs (see Kloft et al, 2021 ; Segura et al, 2021 ). Another example is that in some cases the recovered memories of trauma are in fact continuous memories (i.e., memories of events that people feel they have always known occurred) that have only been reinterpreted as abuse with the time and maturity to understand the event ( McNally and Geraerts, 2009 ; McNally, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…This amnesia had a rapid onset of peak incidence 2–3 min after injection, with effects lasting around 1 h ( Dundee and Pandit, 1972 ). More recently, healthy individuals showed impaired recollection of stories encoded immediately after diazepam administration ( Segura et al, 2021 ). Interestingly, this amnesia is similar to the amnesia in patients with severe medial temporal damage ( Segura et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, healthy individuals showed impaired recollection of stories encoded immediately after diazepam administration ( Segura et al, 2021 ). Interestingly, this amnesia is similar to the amnesia in patients with severe medial temporal damage ( Segura et al, 2021 ). Acknowledging this observation, studying the relationship between BZD use in aging and Alzheimer’s disease (AD) is of great interest, as AD also results in atrophy of the medial temporal lobe.…”
Section: Introductionmentioning
confidence: 99%
“…Taking benzodiazepines during CBT raises clinical concerns, as they may interfere with the intervention components. First, studies have shown that benzodiazepines interfere with episodic memory, producing anterograde amnesia that is more pronounced at higher doses, especially with acute administration (Scharf et al, 1988; Segura et al, 2021; Stewart, 2005). The use of benzodiazepines may therefore interfere with the acquisition of information related to the psychoeducation component throughout the CBT intervention because this medication impacts both learning and memory (Westra et al, 2004).…”
mentioning
confidence: 99%